Genetic characterization of cultivated peanut genetic resources (Arachis hypogaea L.) using microsatellite markers - Pozzi, Florencia Ileana; Etchart, Valeria; Díaz, Daniel; Olegario Manuel, Royo; Díaz, Carolina; Moreno, María Valeria; Gieco, Jorge Omar (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Cultivated peanut (Arachis hypogaea L.) is a crop species of great economic importance, native to South America. It is divided into two subspecies and six botanical varieties. Genetically is an allotetraploid with two duplicated genomes. For genetic characterization of this specie, microsatellite marker would be the most appropriate. The aim of this study was to characterize the genetic variation among cultivated peanut genetic resources belonging to the Active Peanut Germplasm Bank of the Instituto Nacional de Tecnología Agropecuaria (INTA). Twenty five accessions were genotyped with 23 microsatellite markers, of which 17 were polymorphic. Seventy five polymorphic amplified fragments were observed with an average of 4.41 alleles per locus and a range of 1 to 9 alleles. The polymorphic information content was ranged from 0.15 to 0.58. The value of average genetic diversity was 0.165. Cluster analysis and principal coordinate analysis showed two groups, one for representative accessions of fastigiata subspecie and another of the hypogaea. Analysis of molecular variance results showed variance within and between subspecies.